Analisis Pengaruh Bahasa Arab Klasik Terhadap Pemahaman Makna Al-Qur'an - Zulki, Ahmad (SHAWTUL ARAB, 2025)
The Qur'an was revealed in classical Arabic, a language rich in nuances, diction, and unique sentence structures. This language has a very significant influence on understanding the meaning of the Qur'an. Classical Arabic is the key to understanding the meaning of the Qur'an in depth. By studying classical Arabic, we can explore the hidden meanings behind each verse, avoid misinterpretation, and admire the beauty of the language of the Qur'an. However, understanding classical Arabic is not easy and requires continuous effort.